A study on the perceived organizational readiness for change of the librarians and library staff of the University of the Philippines Diliman library system - Palaya, Aiza May V.; Apolinario, Rhea Rowena U. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2015)
Change is pervasive and any institution which aims to carry on with the times is left with no choice but to keep up with it. Change in the workplace may be one of the most challenging subjects to discuss as well as incorporate in previously established routines. Much like any other institution, the library goes through changes.
This study was based on three existing scales, specifically, the Readiness Scale, Commitment to Change Scale, and Resistance Scale which were modified by the researcher to fit the condition of the study. Apart from understanding the perception of the respondents regarding change as a general phenomenon, the author sought to establish the perceived readiness of the respondents to embrace change as well as identify key elements for a successful change implementation. A total of 95 respondents from 28 library units across the University of the Philippines Diliman Library System participated in this study.
Upon analyzing the data, the principal findings of the study are as follows: 1) It appears that 70.5% or 67 of the respondents are familiar with the concept change management while 22 or only 23.2% are not. This very well establishes the notion that most of the staff have come across the concept. 2) Furthermore, 48.4% or 46 of the respondents said that the library exists in a state of rapid and continuous change. 3) Overall, the respondents scored high in change readiness particularly in appropriateness of change implementation. 4) The respondents also scored high in affective commitment which means they are able to identify and associate themselves with their organization. 5) The respondents also have high positive affectivity which means they commonly express positive moods in the performance of their tasks. 6) Majority of the respondents would associate organizational change with "transformation and restructuring". 7) The study also suggests that 24.66% of the respondents consider "misunderstanding the reason for change" as the strongest cause of resistance which may be attributed to lack of communication followed by 19.48% which identified poor communication as a cause of resistance. Meanwhile, technology, according to 39.13% of the respondents is the greatest force that initiates change in their institution. 9) Furthermore, 84.93% of the respondents agree that change in their respective libraries is focused both on the employee and the system.
The researcher provided recommendations for the institution in focus which include conducting regular change readiness assessments, standardizing hiring processes, and involving librarians and library staff in planning and change implementation from the very beginning. Furthermore, the author provided recommendations for future researchers including considering supplementary variables that can affect the individual's perception towards change, such as, gender and civil status, as well as drafting a more robust scale to be used for data gathering which will allow respondents to grasp the goal of the survey more clearly.
In conclusion, it may be inferred that the librarians and library staff of the UPDL System perceive change as a natural phenomenon to which they express affective commitment. The librarians and library staff possess relatively high readiness for change as they deem it appropriate for their respective institution.
Thesis
Keywords: Library employees -- Philippines -- Quezon City; Organizational change -- Philippines -- Quezon City